Pengaruh Model Problem Based Learning Terhadap Kemampuan Berpikir Kritis Siswa Pada Pembelajaran IPS di MTs Islamiyah - Indah Kustina; Mamat Ruhimat; Acep Supriadi (FKIP, Universitas Palangka Raya, 2023)
The research background was the low ability condition on students’ critical thinking. A PBL model was used in the learning process to overcome the problem. PBL is one of the learning approaches that can stimulate students’ critical thinking. The research objective was intended to describe a learning process that used a PBL model to analyze students’ ability to do critical thinking and the influence of the PBL model on students’ ability to do critical thinking. The method used for this research was Quasi Experimental Nonequivalent Control Group Pretest-Posttest Design. The research was conducted in grade VII-B as the experiment class that obtained the PBL model treatment, as well as grade VII-C as the control class that obtained cooperative learning type TGT model treatment. The research instrument was a learning plan, an essay question that consisted of fifteen questions, followed by a validity test, reliability test, difficulty test, and difference of power test. The hypothesis testing result shows 0,043 < 0,05, and N-Gain test shows 1,142 > 1, the conclusion from this research shows that PBL model have influence on increasing the students’ ability to do critical thinking in social science learning